SYSTEMATIC LITERATURE REVIEW: PENGARUH PROGRAM KAMPUS MENGAJAR TERHADAP KESIAPAN MAHASISWA FKIP MENJADI GURU - Aulia, Dewi; Khaerunnisa, Etika; Fakhrudin, Fakhrudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The readiness of students in the Faculty of Teacher Training and Education to become teachers is an important foundation for producing competent educators. However, the quality of teachers in Indonesia is still relatively low, which is partly caused by insufficient preparation among prospective teachers. The Kampus Mengajar program, initiated by the Ministry of Education, Culture, Research, and Technology, was introduced to address this issue. This serves as the basis for conducting this study, which aims to determine whether the Kampus Mengajar program influences students’ readiness to become educators or teachers. Thisstudy employs a Systematic Literature Review method, which involves collecting secondary data in the form of scientific articles, journals, and other relevant sources related to the research topic.The research design involves analyzing, identifying, evaluating, and interpreting 11 articles that discuss the Kampus Mengajar program in nationally accredited journals (SINTA-indexed journals). The findings of this study indicate that the Kampus Merdeka program has a significant influence on students’ readiness to become teachers.